Erratum to: Defining and measuring literacy: facing the reality - Ahmed, Manzoor (© 2011 International Review of Education, 2016)
This erratum was published in the International Review of Education [© Copyright 2011 Elsevier B.V., All rights reserved.] and the definite version is available at : http://doi.org/110.1007/s11159-011-9209-9. The Journal's website is at: http://link.springer.com/article/10.1007%2Fs11159-011-9209-9